Circ_RPPH1 promotes bladder urothelium carcinoma proliferation and EMT by recruiting and binding to EIF4 A3 - HuaWei Liu; JunMin Ma; Xia Yan (Hereditas)
Abstract Background The involvement of circ_RPPH1 in bladder urothelial carcinoma (BUC) remains unclear, as well as the underlying mechanism. Methods Circ_RPPH1 levels in BUC cells and tissues were measured via RT-qPCR. Downregulation of circ_RPPH1 was assessed using colony formation, CCK-8, wound healing, and Transwell assays to evaluate proliferation, migration, and invasion. RIP and RNA pull-down confirmed circ_RPPH1 binding to EIF4A3, while immunoblotting analyzed EIF4A3 and EMT-related proteins. Results High circ_RPPH1 levels in BUC correlated with tumor invasion depth. Its knockout suppressed proliferation, invasion, and EMT, while circ_RPPH1 overexpression reduced EIF4A3 binding to N-cadherin and Vimentin mRNA, promoting EMT. Conclusion Circ_RPPH1 promotes tumor growth and EMT in BUC by inhibiting EIF4A3-mediated mRNA regulation, activating the EIF4A3/N-cadherin/Vimentin pathway.